The impact of gender on students’ choice in selecting a Bachelor’s degree from an International degree programmes offered in Sri Lanka: A Case study (Proceedings of the International Conference on Education, 2019)
Abstract: As the National university intake in Sri Lanka has become progressively competitive over the years, the International Degree Programmes (IDPs) of top-ranked foreign universities emerged in the domestic market to cater to the rising demand for university-level education. Alternatively, those IDPs are mostly offered with higher optionality and flexibility to attract potential students to increase the student enrollment. Thereby, the study mainly discusses the variation of the popularity of the IDPs offered in Sri Lanka within the period from 2011 to 2014. However, the study aims to identify how students select a Bachelor’s degree from IDP based on the subject stream completed for their advanced level and further to identify any significant differences in the decision making criteria gender-wise. Therefore, 694 students (120 in the year 2011, 145 in the year 2012, 187 in the year 2013, 242 in the year 2014) selected from Economics, Management and Social science related Bachelor’s degrees in an IDP and data collected by official documents of the private higher educational institute. The Chi-square test of association was conducted gender-wise to identify the relationship between the subject stream followed for advanced level and the Bachelor’s degree selected. Later, the significant differences have compared within the period from 2011 to 2014. Based on the results, male students show a positive trend in using the optionality when selecting a Bachelor’s Degree from IDP and it is independent of the subject stream completed in advanced level. Alternatively, the decision-making criteria of female students showed differences contrary to male students. Hence the behaviour of students’ needs to be researched and verified in current years to identify significant influences of gender on the decision making process in selecting a Bachelor’s degree from IDPs
Keywords: Bachelor‟s degree; Decision- making process; Gender; International degree programmes